Teaching Reading Comprehension for Slow Learners - Jaenah, Nur (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2024)
This research aims to describe data and information in detail and in depth regarding reading comprehension learning for slow learners at SDN Rambutan 01, East Jakarta. The research method used is a qualitative descriptive method through observation, interviews and documentation, using validity techniques, research persistence and triangulation techniques. The steps to analyze the data using the Milles and Hubberman model through the stages of data reduction, data display, and conclusion drawing/verification of the data and research findings. The results show that the design of reading comprehension learning tries to be adapted to the profile of slow learners, consisting of structuring the planning, process and evaluation stages of reading comprehension learning by educators for slow learners, as well as overcoming learning obstacles, so that learning is more responsive and helps overcoming learning obstacles, practicing academic skills that are lagging behind, increasing personal development, and increasing the learning achievement of slow learners. The explanation of the learning components observed is 1) Planning includes: relaxation of the 2013 curriculum, assessment, objectives, syllabus, lesson plans/ IEP, materials, media, learning resources and learning environment, 2) Process includes coordination between approaches and models, learning strategies, methods and instructions, 3) Evaluation includes aspects of objectives, types, techniques/methods, adaptation, results/implementation, and follow-up. Obtained research conclusions show that SDN Rambutan 01 already has a school policy in managing, compiling, and implementing reading comprehension lessons for slow learners quite well, with notes and continuous efforts to improve the quality of future learning.